Analysis of Slotted E-shaped Microstrip Patch Antenna for Ku Band Applications - Haque, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
In this article, a slotted E-shaped microstrip patch antenna (MPA) is analyzed and proposed that spans the almost whole Ku band frequency range, (13.9 to 18.8) GHz in HFSS and (14.036-17.88) GHz in CST, of satellite communication. The dielectric substrate material Rogers RT/duroid 5880 type with 2.2 dielectric constant and tangent loss of 0.0009 has been utilized. Both length and width of the dielectric substrate are 30 mm. Initially, the suggested antenna's performance has been examined by using HFSS software. The same model is redesigned and tested by using CST to verify the proposed antenna's performance. Based on the findings of two different software tools, the designed slotted E-shaped MPA can be deemed a suitable model for Ku-band satellite communication. Â© 2021 IEEE